Beneficial effects of oral and topical sodium bicarbonate during a battery of team sport-specific exercise tests in recreationally trained male athletes - William H. Gurton; Jordanne Greally; Karolina Chudzikiewicz; Lewis A. Gough; Anthony Lynn; Mayur K. Ranchordas (Taylor & Francis Group, 2023)
Objective This study examined the effects of oral and topical (PR Lotion; Momentous) sodium bicarbonate (NaHCO3) during a battery of team sport-specific exercise tests. Method In a block randomized, crossover, double-blind, placebo-controlled design, 14 recreationally trained male team sport athletes performed a familiarization visit and three experimental trials receiving: (i) 0.3 g·kg−1 body mass (BM) NaHCO3 in capsules + placebo lotion (SB-ORAL), (ii) placebo capsules +0.9036 g·kg−1 BM PR Lotion (SB-LOTION), or (iii) placebo capsules + placebo lotion (PLA). Supplements were given ~120 min prior to the team sport-specific exercise tests: countermovement jumps (CMJ), 8 × 25 m repeated sprints and Yo-Yo Intermittent Recovery Level 2 (Yo-Yo IR2). Blood acid-base balance (pH, bicarbonate) and electrolytes (sodium, potassium) were measured throughout. Rating of perceived exertion (RPE) was recorded after each sprint and post-Yo-Yo IR2. Results Distance covered during the Yo-Yo IR2 was 21% greater for SB-ORAL compared with PLA (+94 m; p = 0.009, d = 0.64) whereas performance was only 7% greater for SB-LOTION compared with PLA (480 ± 122 vs. 449 ± 110 m; p = 0.084). Total completion time for the 8 × 25 m repeated sprint test was 1.9% faster for SB-ORAL compared with PLA (−0.61 s; p = 0.020, d = 0.38) and 2.0% faster for SB-LOTION compared with PLA (−0.64 s; p = 0.036, d = 0.34). CMJ performance was similar between treatments (p > 0.05). Blood acid-base balance and electrolytes were significantly improved for SB-ORAL compared with PLA, but no differences were observed for SB-LOTION. Compared to PLA, RPE was lower for SB-LOTION after the fifth (p = 0.036), sixth (p = 0.012), and eighth (p = 0.040) sprints and for SB-ORAL after the sixth (p = 0.039) sprint. Conclusions Oral NaHCO3 improved 8 × 25 m repeated sprint (~2%) and Yo-Yo IR2 performance (21%). Similar improvements in repeated sprint times were observed for topical NaHCO3 (~2%), but no significant benefits were reported for Yo-Yo IR2 distance or blood acid-base balance compared to PLA. These findings suggest that PR Lotion might not be an effective delivery system for transporting NaHCO3 molecules across the skin and into systematic circulation, therefore further research is needed to elucidate the physiological mechanisms responsible for the ergogenic effects of PR Lotion.